Treatment of corneal neovascularization in ocular chemical injury with an off-label use of subconjunctival bevacizumab: a case report - Iannetti, Ludovico (BioMed Central, 2013)
INTRODUCTION: In this report, we describe the case of a patient with ocular chemical injury, symblepharon, and corneal neovascularization in whom subconjunctival injection of bevacizumab caused regression of corneal opacification and neovascularization, which led to visual improvement. CASE PRESENTATION: A 54-year-old Caucasian woman presented at our eye emergency department following a splash injury of the left eye with sodium hydroxide. At presentation, her visual acuity was light perception. Slit-lamp examination showed diffuse corneal epithelial defects, stromal edema, and localized Descemet’s folds. Despite administration of topical and systemic steroids, she developed symblepharon after 3 months as well as superficial and deep corneal neovascularization with visual acuity 0.5 logarithm of the minimum angle of resolution. A subconjunctival bevacizumab injection (dose 1.25mg/0.05ml) was administered. After 1 week, the vessels appeared thinner and corneal opacity was clearer. Her visual acuity improved to 0.3 logarithm of the minimum angle of resolution. Three weeks later her visual acuity had not changed, and the vessels had started to perfuse again. A second subconjunctival bevacizumab injection was given. After 2 weeks, her vision had improved to 0.1 logarithm of the minimum angle of resolution, vessel regression was observed, and corneal opacity was significantly reduced. Three months after the second injection her vision was unchanged, and the neovascularization remained stable. During the next months, the patient’s condition was well-controlled, and, at the end of follow-up 24 months later, her visual acuity and clinical condition were unaltered. CONCLUSION: Subconjunctival bevacizumab injection may be considered as a second-line treatment of corneal neovascularization caused by chemical injury that is unresponsive to conventional steroid therapy.